Piper aduncum ‘matico’ extract antihypertensive effect on L-NAMEinduced hypertension in mice - Arroyo, Jorge (2012)
Introduction: Piper aduncum also known as matico is credited with antihypertensive, anti-inflammatory, healing effects. Objectives: To determine the antihypertensive activity of Piper aduncum ‘matico’ extract on L-NAME-induced hypertension in mice. Design: Experimental. Setting: Faculty of Medicine, and Faculty of Pharmacy and Biochemistry, National University of San Marcos, Lima, Peru. Biological material: Piper aduncum ethanolic extract leaves and mice. Interventions: Six groups of six Muss musculus mice each were used, one without hypertension (negative control) and four with L-NAME-induced hypertension: one positive control and three groups for 50, 150 and 300 mg/kg doses, respectively. Treatment was given orally once daily for 25 days. Measurements of systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were performed twice weekly (Tuesday and Friday) and measurements between 19 and 23 days of treatment were considered. Main outcome measures: Antihypertensive activity. Results: Higher blood pressure levels were observed at days 19 and 23 in the control and experimental groups that corresponded to measurements 6 and 7. The antihypertensive efficacy to enalapril was 24.1 to 20.6%, followed by matico between 24.9 and 13.7% (p <0.05). Conclusions: Antihypertensive activity of Piper aduncum ‘matico’ extract was demonstrated under experimental conditions.